THE INFLUENCE OF FEB UKI SERVICE QUALITY ON STUDENT SATISFACTION FEB UKI STUDENTS - Amanda , Gloria; Sinaga, Sautman; Sidharta, Juaniva (Universitas Kristen Indonesia, 2022)
This study aims to analyze the effect of service quality consisting of tangible, reliability, responsiveness, assurance and empathy on student satisfaction. FEB is a service market. In this study, it is devoted to students from the 2016-2019 class. The respondents of this study were 89 students who were selected randomly (random sampling). The research instrument used was a questionnaire. Data from the completed questionnaire was then processed using multiple linear regression techniques and hypothesis testing. The results showed that the service quality variables consisting of tangible, reliability, responsiveness, assurance and empathy had a significant effect on student satisfaction. Keywords: service quality, direct evidence, reliability, responsiveness, assurance, empathy, satisfaction, FEB UKI.